Pelaksanaan Program Pembimbingan Kemandirian Klien di Balai Pemasyarakatan Kelas 1 Jakarta Pusat - Ikram , Aprialdi Muharrami Fahrial; Muhammad, Ali (Universitas Pahlawan Tuanku Tambusai, 2023)
Individual and independent guidance for correctional clients is one of the programs to realize integration for correctional inmates. Guidance is carried out in correctional centers. In its implementation, the independence guidance given to correctional clients is based on the results of assessments carried out by community counselors, so that the program runs well for the clients. Implementation of the program at the Class 1 Correctional Center in Central Jakarta contains obstacles, namely the lack of willingness and consistency of clients in following the existing guidance program.